El teletrabajo como herramienta de inclusión para personas con discapacidad en las instituciones públicas del cantón Catamayo, periodo 2023 - Jiménez Soto, Edison Enrique (2024)
The present research work was conducted with the purpose of characterizing the modality of telework as a tool of inclusion for people with disabilities in public institutions in the city of Catamayo. It was structured based on three specific objectives, the first begins with the description of the current situation of the public institutions analyzed and its particularities with respect to telework and access offered by these to people with disabilities; for this a qualitative approach was used, which allowed a detailed analysis of the perceptions and challenges faced by people with disabilities, the data were collected through observation sheets and a questionnaire. In addition, it was investigated whether policies or regulations focused on people with disabilities have been developed, in this section the interview tool applied to 5 human talent officers was considered, the data analysis was performed through a SWOT analysis. It ended with a program that is expected to help promote inclusive work for people with disabilities in public institutions in the canton of Catamayo. As a main result it was determined that people with disabilities do not want to take a telework modality, because many of them prefer to work in a face-to-face environment as it provides important opportunities for social interaction and emotional support, aspects that may be difficult to fully replicate in a virtual environment, the lack of accessibility of remote tools and technologies also constitute barriers that hinder the effective participation of these people, and finally employers can not provide the necessary adaptations for people with disabilities to telework.